Infective Endocarditis in a Tertiary-Center in Jerusalem, an 8-Year Prospective Survey: Effects of Surgery on Mortality. (4th October 2017) - Peretz, Lidor; Korach, Amit; Korem, Maya; Israel, Sarah; Gilon, Dan; Moses, Allon; Strahilevitz, Jacob
Abstract: Background: Use of surgery for the treatment of IE as related to surgical indications and operative risk for mortality has not been well defined. Although cardiac surgery can be life-saving, it also carries significant risk for the patient. Our aim was to evaluate the effect of surgery on survival. Methods: A prospective observational cohort study of consecutive adult patients with definite IE according to the modified Duke criteria. Data were collected from January 2009 through June 2016 following a predefined case report form designed by the International Collaboration on Endocarditis Prospective Cohort study group. Indications for surgery were categorized following current guidelines. Results: Among 165 IE episodes, 104 (63%) were community acquired. 93 (56%) involved native valves. The predominant causative microorganism was Staphylococcus aureus ( n = 56). Mean Charlson comorbidity score was 4.4 (median 4.0, SD 3.1). Overall in-hospital mortality was 20.6%. 84 of 165 patients had no indication for surgery, 44 underwent surgery and 37 who had an indication were treated conservatively due to a contraindication for surgery. In-hospital and 6-month mortality rates among the three groups were: 14.3%, 6.8%, 51.4% and 31%, 22%, 61.1%, respectively (among the conservative treatment groups, P < 0.001). Overall six months mortality rates were significantly lower among the surgically treated group compared with the conservatively treated group (22% vs. 40.4%, P = 0.048), whereas mortality rates among primary conservative and surgically-treated patients were similar. In-hospital mortality rates among groups of patients refused operation because of poor risk regardless of surgery, patients who had a stroke, and those with a soft contraindication were 71%, 18% and 0%, respectively, P = 0.04. Among the patients who underwent surgery, of the 39 patients with a strong indication for surgery, three died during hospitalization whereas none of the five patients with a weaker indication died. Conclusion: Compared with our previous cohort, we observed a lowered mortality rate, similar to contemporary population-based studies. Surgery was associated with increased survival. Careful evaluation and assessment of contraindications to surgery is warranted. Disclosures: All authors: No reported disclosures.